Design for longevity: taking both the material and social aspects of product-life into account. (1st January 2014) - Hebrok, Marie
The aim of this paper is to explore how knowledge provided by social science research on the dis-domestication of products can inform design for longevity. The research presented is an investigation into the dis-domestication of objects from the household. Dis-domestication is a concept developed by Hebrok (2010) and pertains to the process in which products go out of use and are being disposed of. The concept has been developed as an addition to the framework of domestication by Silverstone et al. (1992), which is also the starting point of the analysis provided by this paper. The product group that serves as a case for the analysis is furniture. Prolonging the lifespan of products is vital in order to decouple economic success from environmental impact. This paper explores the fruitfulness of applying methods from social science and the framework of domestication to the study of disposal behaviour in a design perspective.